Pengambangan dan Validasi Video Animasi sebagai Media Edukasi dalam Pemberian Makanan Pendamping ASI (MP-ASI) pada Baduta - Putri, Athira Salsabila; Kurnia, Pramudya; Firmansyah, Firmansyah (Dinasti Research, 2025)
The limited knowledge of mothers regarding the provision of complementary feeding (MP-ASI) is one of the factors contributing to nutritional issues in toddlers. Therefore, the development of educational media is necessary to enhance mothers' understanding of MP-ASI. This study aims to design and assess the feasibility of an animated video as a learning medium for MP-ASI provision. The research employs a Research and Development (R&D) approach using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The developed media was then validated by three content experts and three media experts, followed by a field test involving 30 mothers of toddlers. Data collection was conducted using a validation form designed by the researcher, with the Content Validity Index (CVI) threshold for the validation test set between 0.8 and 1.0, while the field test results ranged between 85% and 100%. The findings revealed that content specialists assigned a Content Validity Index (CVI) of 1.0, while media professionals also rated it at 1.0, signifying the media’s appropriateness for application. Additionally, the field trial yielded a score of 88.16%, categorizing it as highly viable for educational purposes. From these analytical outcomes, it can be inferred that the animated video is both valid and appropriate for use as an instructional resource to improve mothers’ understanding of complementary feeding (MP-ASI).